MPROVEMENT OF THE DIAGNOSTIC METHOD HIGH VOLTAGE INPUTS OF OIL SWITCHES FOR RESULTS OF GAS CHROMATOGRAPHIC ANALYZES TRANSFORMER OILS - ZAITSEV, SERGEY; KISHNEVSKY, VICTOR (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article presents the results of improving the method for diagnosing high-voltage oil-filled oil circuit breaker bushings based on the results of gas chromatographic analyses of samples of operational mineral transformer oils. The aim of the study is to ensure the reliability of operation of high-voltage oil-filled oil circuit breaker bushings by improving the method of diagnosing these bushings based on the results of gas chromatographic analysis of samples of mineral transformer oils. The objects of research were methods for diagnosing high-voltage oil-filled oil circuit breaker bushings based on the results of gas chromatography analysis of mineral transformer oil samples to determine the content of dissolved diagnostic components. The subjects of the study were samples of mineral transformer oils from high-voltage oil-filled bushings of the BMV-110/2000U1 and BMVU-110/2000U1 types installed on oil circuit breakers of the U-110 and MKP-110 types. The main conclusions of the research were obtained: 1. It was determined: a) in samples of mineral transformer oils, the content of such dissolved diagnostic components as: H2, CH4, C2H6, C2H4, C2H2, CO, CO2, O2, N2, H2O; additive "Ionol"; furan compounds (2-furyl alcohol; 2-furfural; 2-acetylfuran; 5-methyl-2-furfural); b) the effect of temperature from 60 0C to minus 20 0C on the solubility of hydrogen and air in samples of mineral transformer oils. 2. The improved algorithm for diagnosing high-voltage oil-filled oil inlets of oil circuit breakers based on the results of gas chromatographic analyses of samples of mineral transformer oils includes the following procedures: a) control of the content of dissolved gases, furan compounds, the additive "Ionol", water in these oils; b) diagnosis of high-voltage oil-filled oil inlets of oil circuit breakers using such methods as: "Limit level of concentrations", "Table method", "Graphic images of defects", "ETRA", "Duval triangle", "Visual inspection after disassembly of high-voltage oil-filled bushings". The obtained results allow to increase the reliability of diagnostics of high-voltage oil-filled bushings of oil circuit breakers.